Eloquent Images : Evangelisation, Conversion and Propaganda in the Global World of the Early Modern Period - Capriotti, Giuseppe (Book collections on Project MUSE., 2022)
Drawing on original research covering different periods and spaces, this book sets out to appreciate the specific place of images in the history of evangelisation in the long modern period. How can we reconceptualise the functions of the visual mediation of the gospel message, both in terms of the production and reception of this message and in terms of its effective mediators, artists, religious, and cultural ambassadors? The contributions in this book offer multiple geographical and historical insights regarding the circulation of the image on the global scale of the Christianised world or the world in the process of being Christianised, from China to Iberia. Combining the contribution of historians and art historians, the authors highlight the points of intercultural encounter and tension around preaching, catechesis, devotional practices and the propagandistic use of images. Through its aesthetic and social study of the image, and by examining the inner and outer borders of Europe and the mission lands, 'Eloquent Images' contributes significantly to the history of evangelisation, one of the major dynamics of the first European globalisation.